MAKNA EKOTEOLOGIS TRADISI NUNI DAN SAEF PADA MASYARAKAT DAWAN DITINJAU DARI PERSPEKTIF LAUDATO SI’ ARTIKEL 84-88 - Atu, Laurentius Florido; Benggu, Wilhelmus (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
Currently, the world is suffering from an ecological crisis. The crisis results from human behavior that tends to be destructive towards nature. Humans regard themselves to be in control of other creatures. Nature is seen only as an entity created to serve all their needs. Faced with this situation, Pope Francis through his Encyclical Laudato Si' calls for the importance of re-reflecting harmony among all creation in the light of faith and revelation. He highlights the fact that there is an integral relationship among humans, other elements of creation, and God. In fact, this way of seeing things has already existed in certain local wisdom, such as the ‘nun’i and ‘saef’ traditions in the Dawan community. This essay purports to examine the ecotheological meaning of the two local traditions. The method used to collect data is a qualitative one with interviews and literature studies. The finding of this study is that the nuni and saef traditions embody respect for nature. The respect emerges from an awareness that nature has been playing an important role in the life history of the Dawan people. Nature, furthermore, is desribed as a part of God as well as a locus of His presence. Thus, the respect for nature leads them to a relationship with God the Creator. Between the two local wisdom (nuni and saef) and Laudato Si', there exists the same value with regard to the relationship between humans, nature, and God.